Epidemic of Invasive Pneumococcal Disease, Western Canada, 2005–2009 - Tyrrell, Gregory J.; Lovgren, Marguerite; Ibrahim, Quazi; Garg, Sipi; Chui, Linda; Boone, Tyler J.; Mangan, Carol; Patrick, David M.; Hoang, Linda; Horsman, Greg B.; Van Caeseele, Paul; Marrie, Thomas J.
In Canada before 2005, large outbreaks of pneumococcal disease, including invasive pneumococcal disease caused by serotype 5, were rare. Since then, an epidemic of serotype 5 invasive pneumococcal disease was reported: 52 cases during 2005, 393 during 2006, 457 during 2007, 104 during 2008, and 42 during in 2009. Of these 1,048 cases, 1,043 (99.5%) occurred in the western provinces of Canada. Median patient age was 41 years, and most (659 [59.3%]) patients were male. Most frequently representing serotype 5 cases (compared with a subset of persons with non-serotype 5 cases) were persons who were of First Nations heritage or homeless. Restriction fragment-length polymorphism typing indicated that the epidemic was caused by a single clone, which multilocus sequence typing identified as sequence type 289. Large pneumococcal epidemics might go unrecognized without surveillance programs to document fluctuations in serotype prevalence.